Meningkatkan Hasil Belajar Siswa Tentang Sistem Tata Surya Melalui Permainan Kartu Bergambar di SDN 3 Sukamenak - Rini Rini; Caswita (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
The teacher's incompatibility in applying learning techniques or models causes student learning outcomes in the Solar System material to not reach the Minimum Completeness Criteria (KKM). So we need an effort to overcome this problem, one of which is by using picture card games. This research aims to obtain an appropriate model for planning and implementing learning about the Solar System using picture card games and determine the improvement in student learning outcomes. This research uses the Kemmis and Mc.Taggart Classroom Action Research method which consists of 3 cycles. This research was carried out in class VI of Sukamenak 3 Elementary School which consisted of 23 students. The research results showed that the average student learning outcome was 71 in cycle 1, after cycle 2 the score was 80.8, while in cycle 3 the average was 87.8. This research concludes that student learning outcomes regarding the Solar System using picture card games have improved well.